Penerapan Model Eliciting Activities untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis dan Self Confidence Siswa SMA - Yuli Amalia; M. Duskri; Anizar Ahmad (Universitas Syiah Kuala, 2015)
The ability of mathematical creative thinking and self-confidence are ones of the targets in mathematics learning. Therefore, learners need a relevant model to have them be active in searching information themselves, group working, building self-confidence, and improving creative thinking in perceiving and understanding the information to resolve a problem. One of the models is model-eliciting activities to improve students mathematical creative thinking and self-confidence to have students organize their own knowledge in learning. Applying this model, this research was to investigate (1) the differences of students mathematical creative thinking improvement through dividing into low, medium, and high subgroups, (2) the description of students self-confidence in mathematics learning, and (3) the correlation of creative thinking ability and self-confidence in mathematics learning. This experiment used one-group pretest-posttest design. The population was all first year students of SMA Negeri 5 Banda Aceh, and the sample was all students in Class X-IA3. The instruments applied in the research were mathematical creative thinking ability test and self-confidence questionnaire. The statistic testing applied in data analysis was the average difference test, whereas the questionnaire was counted based on the percentage. The result obtained showed that the improvement in students mathematical creative thinking exists in those who applied model-eliciting activities. While, the result from the questionnaire proves that the majority of the students (74.6%) establish positive view toward mathematics learning using model-eliciting activities. In contrast, there was no any correlation between creative thinking ability and self-confidence in mathematics learning.